2020
DOI: 10.1111/plb.13209
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pollination, herbivory and autonomous selfing on the maintenance of flower colour variation inSilenelittorea

Abstract: Intraspecific flower colour variation has been generally proposed to evolve as a result of selection driven by biotic or abiotic agents. In a polymorphic population of Silene littorea with pink‐ and white‐flowered plants, we studied pollinators, analysed flower colour perception and tested for differences in pollinator visitation. We also experimentally analysed pollinator limitation in fruit and seed set, and the degree of autonomous selfing. The incidence of florivory and leaf herbivory was compared over 3–4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 88 publications
(113 reference statements)
0
11
0
Order By: Relevance
“…However, in Barra, the higher flower production was found in plants with darker flowers that consequently produced more seeds. Previous studies had found autonomous selfing in S. littorea, although pollinator visitation was required to reach full seed-set (Casimiro-Soriguer et al, 2015;Buide et al, 2020). In Barra population, Buide et al (2020) reported that pollinators preferably visited pink flowers, and white-flowered plants under free pollination reached fruit-set values similar to those obtained by autonomous selfing.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…However, in Barra, the higher flower production was found in plants with darker flowers that consequently produced more seeds. Previous studies had found autonomous selfing in S. littorea, although pollinator visitation was required to reach full seed-set (Casimiro-Soriguer et al, 2015;Buide et al, 2020). In Barra population, Buide et al (2020) reported that pollinators preferably visited pink flowers, and white-flowered plants under free pollination reached fruit-set values similar to those obtained by autonomous selfing.…”
Section: Discussionmentioning
confidence: 75%
“…Previous studies had found autonomous selfing in S. littorea, although pollinator visitation was required to reach full seed-set (Casimiro-Soriguer et al, 2015;Buide et al, 2020). In Barra population, Buide et al (2020) reported that pollinators preferably visited pink flowers, and white-flowered plants under free pollination reached fruit-set values similar to those obtained by autonomous selfing. Thus, the lower male and female fitness of white-flowered plants in Barra could be related to their lower pollinator attraction, but the lower fitness seems mainly due to their lower flower production.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations